2019
DOI: 10.1002/jms.4329
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation pathways of protic ionic liquid clusters: Alkylammonium nitrates

Abstract: Protic ionic liquids are promising candidates for many applications, including as spacecraft propellants. For both fundamental interest and understanding clustering and dissociation during electrospray‐based propulsion, it is useful to explore the dissociation pathways of protic ionic liquid clusters, as well as the factors affecting the relative contributions of each pathway to the observed MS/MS spectra. With that said, most of the published reports on ionic liquid cluster dissociation have focused on aproti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Recently, the dissociation of protic ionic liquid clusters has been investigated. Protic ionic liquid clusters have many additional dissociation channels – summarized in Figure – so the primary goal of these first papers was to investigate which pathways were active and with what relative intensities for model systems, namely alkylammonium nitrates, and for the ionic liquid propellant 2‐hydroxyethylhydrazinium nitrate . In general, proton transfer mediated dissociation was indeed observed for both systems.…”
Section: Current Contributions From Mass Spectrometrymentioning
confidence: 99%
“…Recently, the dissociation of protic ionic liquid clusters has been investigated. Protic ionic liquid clusters have many additional dissociation channels – summarized in Figure – so the primary goal of these first papers was to investigate which pathways were active and with what relative intensities for model systems, namely alkylammonium nitrates, and for the ionic liquid propellant 2‐hydroxyethylhydrazinium nitrate . In general, proton transfer mediated dissociation was indeed observed for both systems.…”
Section: Current Contributions From Mass Spectrometrymentioning
confidence: 99%
“…Cluster dissociation studies have investigated relative interaction strengths of common cations and anions. 20,[37][38][39] Additionally, the dissociation of protic ionic liquid clusters, specifically comprised of 2-hydroxyethylhydrazinium nitrate 40 or alkylammonium nitrates, 41 has also been investigated and contrasted with the clustering and dissociation of aprotic ionic liquids. Gas-phase cation dissociation has been studied, 42 including with a focus on specific classes such as zwitterions 43 and sulfur-containing cations.…”
Section: Previous Mass Spectrometric Studies Of Ionic Liquidsmentioning
confidence: 99%
“…Interactions with UV solar photons are likely to be one of the major causes of chemical breakdown in these plumes and, as such, it is imperative to understand the photochemical reactions occurring in the space environment. Plumes resulting from IL thrusters are initially composed of charged IL clusters, which can dissociate into neutral pairs, bare ions, or neutral molecules. Recent studies by Patrick et al , and Prince et al focused on the decomposition of such charged IL clusters and found that many lose ion pairs as the dominant product. After these plumes are formed, questions regarding the eventual fate of the ion pairs are does UV radiation cause the ion pairs to become radicals via electron transfer, decompose directly into ions, or break chemical bonds in the component ions to produce smaller ions/neutrals?…”
Section: Introductionmentioning
confidence: 99%